2021
DOI: 10.1002/eji.201948358
|View full text |Cite
|
Sign up to set email alerts
|

Enriched environment enhances NK cell maturation through hypothalamic BDNF in male mice

Abstract: Macroenvironmental factors, including a patient's physical and social environment, play a role in cancer risk and progression. Our previous preclinical studies have shown that the enriched environment (EE) confers anti‐obesity and anti‐cancer phenotypes that are associated with enhanced adaptive immunity and are mediated by brain‐derived neurotrophic factor (BDNF). Natural killer (NK) cells have anti‐cancer and anti‐viral properties, and their absence or depletion is associated with inferior clinical outcomes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…The spleen, bone marrow and blood of mice living in the environment have a higher proportion of Natural killer cells (NK), and EE-stimulated tumour-bearing mice have observed increased maturity of NK cells ( 37 ). Overexpression of BDNF in the hypothalamus replicates the EE-induced NK cell phenotype, while the knock-out of BDNF in the hypothalamus abolishes EE-induced NK regulation ( 38 ). In addition, BDNF is also involved in EE-induced T cell regulation in primary and secondary lymphoid tissues, including the reduction of the total number of splenic T cells and the change (ratio Decrease) of CD4 T helper to CD8 cytotoxic T lymphocytes (CTL) in secondary lymphoid tissue (SLT) ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…The spleen, bone marrow and blood of mice living in the environment have a higher proportion of Natural killer cells (NK), and EE-stimulated tumour-bearing mice have observed increased maturity of NK cells ( 37 ). Overexpression of BDNF in the hypothalamus replicates the EE-induced NK cell phenotype, while the knock-out of BDNF in the hypothalamus abolishes EE-induced NK regulation ( 38 ). In addition, BDNF is also involved in EE-induced T cell regulation in primary and secondary lymphoid tissues, including the reduction of the total number of splenic T cells and the change (ratio Decrease) of CD4 T helper to CD8 cytotoxic T lymphocytes (CTL) in secondary lymphoid tissue (SLT) ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study reported that housing rats in an EE after occlusion of the middle cerebral artery enhances sensorimotor recovery by decreasing BDNF mRNA and protein levels, 68 which is different from the previous report and our current findings. 69 We suggest that the discrepancy may be related to the animal models used and the measurement protocol. Heme oxygenase-1 (HO-1) and the BDNF-mediated pathway are involved in the pathophysiology of depression.…”
Section: Discussionmentioning
confidence: 94%
“…In agreement, splenectomy abrogates the EE-induced tumor-resistant phenotype ( 35 ) implicating splenocytes in tumor resistance. EE also impacts the recovery of NK cells after depletion ( 37 ). We observed a faster NK-cell recovery in the spleen, bone marrow and blood following depletion using anti-asialo-GM1 antibody ( 37 ).…”
Section: Environmental Enrichment Influences Nk Cell Functionmentioning
confidence: 99%
“…EE also impacts the recovery of NK cells after depletion ( 37 ). We observed a faster NK-cell recovery in the spleen, bone marrow and blood following depletion using anti-asialo-GM1 antibody ( 37 ).…”
Section: Environmental Enrichment Influences Nk Cell Functionmentioning
confidence: 99%
See 1 more Smart Citation